2019
DOI: 10.1111/nep.13400
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of regret in elderly dialysis patients

Abstract: Although majority of elderly dialysis patients were comfortable with their decision to start dialysis, a proportion was ambivalent or regretted this choice. Regret was more likely among those who experienced decisional conflict and/or expressed poorer information satisfaction. Healthcare professionals should recognize these risk factors and take steps to minimize chances of regret among this population subset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…The incurability of kidney failure forces patients to reinvent themselves, make compromises or adopt beliefs or behaviours discordant with medical opinion 47–50. Despite these burdens, the majority of patients reported satisfaction with treatment and improvement of symptoms; another study found that the majority of patients reported no decision regret or ambivalence about starting dialysis 51 52. It should be noted, however, that patients’ decisions, goals and expectations are not static but change with time as different issues emerge 42 53…”
Section: Resultsmentioning
confidence: 99%
“…The incurability of kidney failure forces patients to reinvent themselves, make compromises or adopt beliefs or behaviours discordant with medical opinion 47–50. Despite these burdens, the majority of patients reported satisfaction with treatment and improvement of symptoms; another study found that the majority of patients reported no decision regret or ambivalence about starting dialysis 51 52. It should be noted, however, that patients’ decisions, goals and expectations are not static but change with time as different issues emerge 42 53…”
Section: Resultsmentioning
confidence: 99%
“…As ESRD patients and their caregivers navigate these choices, there is a need for supportive, contextually appropriate decision‐making aids to enable informed decision making. Evidence from Singapore has shown that lack of knowledge of CM and deference to physician recommendations may lead older ESRD patients to seek dialysis and that a small proportion of patients later regret their decision to start dialysis . Work done elsewhere has also shown that most older patients have unrealistic expectations of dialysis upon commencing treatment, and has suggested the need for age‐specific information tailored to older ESRD patients that clearly communicate the risks, benefits and burdens associated with dialysis …”
Section: Introductionmentioning
confidence: 99%
“…Evidence from Singapore has shown that lack of knowledge of CM and deference to physician recommendations may lead older ESRD patients to seek dialysis 10 and that a small proportion of patients later regret their decision to start dialysis. 11 Work done elsewhere has also shown that most older patients have unrealistic expectations of dialysis upon commencing treatment, 12 and has suggested the need for age-specific information tailored to older ESRD patients that clearly communicate the risks, benefits and burdens associated with dialysis. 13 Presently, there is limited research exploring the treatment decision-making process of older ESRD patients and caregivers, and the majority of current literature is centred on Western populations.…”
Section: Introductionmentioning
confidence: 99%
“…Even in people who commence dialysis, decision regret could be measured over the first 3–6 months to detect whether changes occur over time once the realization of the actual burden of dialysis on every day develops. In a recent study, decision regret was associated with older age and significantly associated with longer duration on dialysis (Tan, Teo, Finkelstein, & Chan, ). Additionally, in this same study, those people who had lower satisfaction with the information provided were more likely to experience decision regret (Tan et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study, decision regret was associated with older age and significantly associated with longer duration on dialysis (Tan, Teo, Finkelstein, & Chan, ). Additionally, in this same study, those people who had lower satisfaction with the information provided were more likely to experience decision regret (Tan et al, ). Both our study and Tan et al suggest that the use of a DSI such as OPTIONS could have a role in lowering decision regret.…”
Section: Discussionmentioning
confidence: 98%